Humeral head histopathological changes in cuff tear arthropathy. (4th December 2018) - Toma, Takashi; Suenaga, Naoki; Taniguchi, Noboru; Oizumi, Naomi; Yamaguchi, Hiroshi; Tome, Yasunori; Kanaya, Fuminori
Purpose: The aim of this study was to investigate the histopathological changes in the humeral head in cuff tear arthropathy (CTA) compared with those in glenohumeral osteoarthritis (OA) and humeral neck fracture, which served as non-cuff tear controls. Methods: Twenty-three humeral heads extracted at the time of shoulder prosthesis arthroplasty between June 2014 and July 2015 were evaluated in the present study. The diagnoses included four-part humeral neck fracture ( n = 4; average age, 85.0 years), glenohumeral OA ( n = 4; average age, 71.0 years), and CTA ( n = 15; average age, 73.0 years). The humeral heads were evaluated pathologically by hematoxylin and eosin and Safranin-O staining, and the thickness of the articular cartilage was measured. Results: Fibrillation, thinning, and tearing of the cartilage were observed in the superior area of the humeral heads in CTA and glenohumeral OA. In CTA cases, clusters of chondrocytes in the cartilage were observed. Moreover, the thickness of the cartilage layer in the middle of the humeral head was 1.54 ± 0.07, 0.32 ± 0.46, and 2.19 ± 0.50 mm in humeral neck fracture, glenohumeral OA, and CTA, respectively. The cartilage layer in CTA was thicker than that in glenohumeral OA (CTA vs. OA: p < 0.05). Conclusion: OA changes in the superior area of the humeral heads and thickening of the cartilage layer from the middle to the inferior of the humeral heads were confirmed histopathologically, suggesting that simultaneous mechanical and nutritional factors might be contributing to CTA pathogenesis. The current study provided the better understanding of cartilage damage and thickening in CTA. This will help guide treatment options in the setting of CTA.